(untitled) (Journal of Preventive and Social Medicine, 2024)
Background: Since early May 2022, the unprecedented outbreak of human monkey pox (HMPX) has been documented globally which demands assessment of knowledge on the emerging viral infection as well as the state of conspiracy belief among the healthcare professionals. The present study aimed to assess the knowledge about HMPX and its relation to conspiracy belief. Methods: This cross-sectional study was conducted at the Combined Military Hospital Dhaka (CMH) among purposively selected 254 healthcare professionals from July 2022 to September 2022. Data were collected through face-to-face interview using a pre-tested semi-structured questionnaire with validated and reliable tools. Results: The study comprised a total of 254 respondents, including 53.9% male, 72.8% respondents having a graduate degree and 42.9% individuals aged between 26-30 years. The study revealed very poor (61.8%) knowledge on HMPX as well as higher (50.4%) belief in conspiracy theory among the respondents. The hierarchical logistic regression revealed that male had significantly higher (B=1.12, OR 3.06, 95% CI=1.714-5.463) knowledge on HMPX virus than that of the female, age group <31 years emerged as a negative and significant predictor than that of the age group >31 years (B= -1.065, OR 0.345, 95% CI=0.172-0.690), monthly income of between 60001-90000 taka also emerged as a positive and significant predictor than that of the income of >90001 taka (B=0.763, OR 2.145, 95% CI=1.002-4.595). Conclusion: The study findings demand intervention of appropriate health educational program in the medical study curriculum. JOPSOM 2023; 42(1):29-39